ANALYSIS THE EFFECT OF PRIMARY COIL LENGTH OF TRANSFORMATOR TO THE RESULTED ELECTROMOTIF FORCE - Bowo Eko Cahyono; Muhammad Syukron Ali; Supriyadi Supriyadi (Spektra: Jurnal Fisika dan Aplikasinya, 2019)
Transformator is an electrical device that uses a principle of solenoid wrapped in kern, and there are usually two or more coils. Each coil of the taranformator is electromagnetically connected. The transformator is made to fulfill the specific level of voltage required in the devices or systems that use alternating current electrical energy. For example, transformator tap change is design to have different number of primary turns to produce a fixed output voltage, in term there is a changing in the input voltage. This research tries to analyze the effect of the length of primary coil difference of transformator to the voltage resulted in the secondary coil. The objective of the study is producing a relationship of primary coil length variation to the resulting voltage. Variation of coil length is made from 1 cm to 15 cm with interval of 1 cm coil length. The length of the secondary coil is also varied imto 3 cm, 6 cm, and 9 cm. The test is performed by providing the same input voltage at each variation of the primary coil length and then measure the output voltage. The results show that the longer primary coil will produce the smaller output voltage in the secondary coil of tranformator. Based on the resulted graph, the relationship of the length variant of primary coil is linear to the voltage measured in the secondary coil.with determination coefficient (R2) of 0.9603, 0.9775, and 0.9822 respectively forlength of 3 cm, 6 cm, and 9 cm of the secondary coil.